Penerimaan dan Dukungan Keluarga Penyandang Disabilitas Rungu Wicara: Studi Pada Unit Informasi dan Layanan (uils) Koja - Shabrina Riana; Musahwi; Nurlaili Khikmawati (Jurnal Pelayanan Pastoral, 2025)
This study discusses how families deal with the reality that their children have speech disabilities or cannot speak normally. The main issue examined in this study is how families accept and support children with speech disabilities, as well as how social institutions such as the Koja Social Information and Service Unit (UILS) help families form new meanings for disability. This study aims to examine the process of acceptance and forms of family support for children with speech and hearing disabilities at the Social Information and Service Unit (UILS) in Koja. This study uses a qualitative approach with a case study method. The results of the study were obtained through observation and semi-structured interviews. The theory used in this study is George Herbert Mead's Mind, Self, and Society theory. The results of the study show that the family acceptance process takes place in stages, from rejection to full acceptance, influenced by economic, cultural, spiritual, and social stigma factors. From the perspective of George Herbert Mead's Mind, Self, and Society theory, the identity of the child and family is shaped through social interaction, symbols, and support received from the environment. The conclusion of this study is the importance of striving to create a supportive and positive environment for the acceptance of people with disabilities, specifically an environment like the social institution Unit Informasi dan Layanan Sosial (UILS) Koja as an agent of transformation in shaping collective meaning and family acceptance of hearing and speech disabilities.